Can Antinuclear Antibodies Have a Pathogenic Role in Systemic Sclerosis? - Aurélien Chepy; Aurélien Chepy; Louisa Bourel; Vincent Koether; Vincent Koether; David Launay; David Launay; Sylvain Dubucquoi; Sylvain Dubucquoi; Vincent Sobanski; Vincent Sobanski; Vincent Sobanski (Frontiers in Immunology, 2022)
Systemic sclerosis (SSc) is a connective tissue disease characterized by extensive fibrosis of the skin and internal organs, associated with vasculopathy and autoimmune features. Antinuclear antibodies (ANA) are found in almost all SSc patients and constitute strong diagnosis and prognosis biomarkers. However, it remains unclear whether ANA are simple bystanders or if they can have a role in the pathophysiology of the disease. One might think that the nuclear nature of their targets prevents any accessibility to autoantibodies. Nevertheless, recent data suggest that ANA could be pathogenic or at least contribute to the perennation of the disease. We review here first the indirect clues of the contribution of ANA to SSc: they are associated to the disease subtypes, they may precede disease onset, their titer correlates with disease activity and severity, there is an association between molecular subsets, and some patients can respond to B-cell targeting therapy. Then, we describe in a second part the mechanisms of ANA production in SSc from individual genetic background to post-transcriptional modifications of neoantigens. Finally, we elaborate on the potential mechanisms of pathogenicity: ANA could be pathogenic through immune-complex-mediated mechanisms; other processes potentially involve molecular mimicry and ANA penetration into the target cell, with a focus on anti-topoisomerase-I antibodies, which are the most probable candidate to play a role in the pathophysiology of SSc. Finally, we outline some technical and conceptual ways to improve our understanding in this field.